Upper and Lower Respiratory Tract Infections: One Year Based Observational Study in Pediatric Population - Imran Ahmed, Naheed Haroon Kazi,Sikandar Ali Bhand, Yasirarfat Memon (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Pediatric population is the most common among the populations at higher risk for infections and respiratory infections are the most common among the infections due to many reasons. Aim: To assess the nature of various respiratory infections in pediatric population. Study Design: Cross sectional study. Place and duration of study: Department of Pediatrics, Muhammad Medical College Hospital, Mirpur Khas from 1stJanuary 2018 to 31st December 2018. Methodology: Two thousand and ninety nine children with respiratory illness were included irrespective gender. Results: The males were more affected 1175 (56%) in comparison to 924 (44%) females and most cases were below the age of 5 years age 1428(68%) whereas children above the age of 5 years were 671 (32%). Common upper respiratory tract infections observed were pharyngitis, tonsillitis and otitis media which were collectively 1576 (75.10%) of the cases followed by lower respiratory tract infections (pneumonia) which was found in 523 (24.90%) patients. Conclusion: Upper respiratory infections were more common than lower respiratory infection in children and males are more affected than females.